Від Музею румунського села – до Національного музею села імені Дімітрія Густі - Попою, П. (Народна творчість та етнологія, 2011)
The complex museum of rural architecture and traditional technology is representative of the entire Romanian folk creation of the last three centuries. The museum now includes 346 buildings (farmhouses, stables and shelters for animals, barns, cellars, wells, fences an gateways, preaching crosses, churches, mills, rustic devices, workshops) with characteristic inventories. The «Dimitrie Gusti» National Village Museum, a prestigious institution with over 80 years of experience, is one of the first open air museums in Europe. It is the result of intensive and sustained research, both theoretical and in the field, as well as museological experiments, coordinated by Professor Dimitrie Gusti, the founder of the Sociology School in Bucharest.